Information Systems in Management Science - Stern, Harry (Management Science, 1970)
The lack of application of computer technology to medical service is worthy of note. Although there is a great deal of discussion and an obvious need, there have been precious few successful applications of computers to the solution of large scale medical problems. One area of modest success is that of on-line control. Patient monitoring is widely accepted, and the interfacing of laboratory equipment (such as Technicon's SMA 12 or the Aga's Auto Chemist) is well accepted. However, the total problems of “patient management” have not been successfully attacked.